Grey-Water Treatment and Reuse: A Review - Prashanna Rangan, R.; Heenalisha, K. (Asian Journal of Science and Applied Technology, 2019)
Globalization as well as Rapid industrialization had made an evil impact and led to the over usage of water, since it has been raised drastically in the last decade. This increase in water demand has led to a situation at which humans find difficulty in availing the water for their needs. There has been a great technological research been conducted on waste water recycling methods. Grey-water is a form of waste water, consisting of kitchen water, bathrooms, dish and cloth washers. Reusing of Grey-water has become a better choice, but since the amount of dissolved contents are unknown, it is mandatory to recycle before reuse. Since Grey-water is less in organic and BOD content and free from faecal matter for reproduction of bacteria, it could be recycled easily by adapting various techniques. The recycled water may be used for many regenerative purposes, say irrigating the agricultural lands, toilet flushings, home garden watering, etc. this paper aims in revolving the possible techniques that can be utilized for recycling the grey-water.